(untitled) (diségno, 2024)
The ‘panoramas’, painted canvases intended to be exhibited in cylindrical buildings named ‘rotundas’, were produced by the composition of images portrayed from the same point of view, rotating the direction of the visual axis. The privileged subjects of panoramas were urban areas, usually portrayed from an observation point placed at a high altitude, usually a tower, a bell tower, or the roofs of a building. In panoramas, the city cannot be seen at a glance, as the overall image can be formed only in the observer’s memory, as a combination of the partial views of the cylindrical canvas. In order to remedy this difficulty, or simply to help visitors to recognise the depicted places, panoramas were also represented in a synthetic image, produced by the projection of the cylindrical canvas onto a horizontal plane; these images were called ‘horizontal panoramas’. This essay analyses the projective relationship between the cylindrical panorama and the horizontal panorama; unfortunately, as far as the authors know, the two images have been preserved only in two panoramas: the panorama of Constantinople, realised in 1801 by Henry Barker, and the panorama of Thun, realised in 1814 by Marquard Wocher. The analysis of the correspondences between the cylindrical and the horizontal panorama is anticipated by the survey of 17th century treatises that illustrate the problem of the relationship between a cylindrical image and its projection onto a plane. One hypothesis proposed in this study is that the hollow area in the centre of horizontal panoramas may be the base of a cylinder whose surface shows the image of the cylindrical panorama formed by reflection.